Orion's guiding stars : the myth of the hero and the human instinct for story - Ladewig, Marc (Algora Publishing, 2017)
The myth of the hero, the grand motif of folklore, is a three-part story that is found in human cultures across time and terrain, ever since we were hunter-foragers. Here, a veteran teacher shows that the myth of the hero best reveals itself through a jewel of many facets rather than a single clear lens. You have to stand back at the proper distance from the painting in order to see the myth of the hero pop out. He explores the essential features of the myth, where these stories came from and what they are really about, and analyzes how regular people see these stories, revealing an unexamined.